Fabrikasi Sel Surya Berbasis Bahan Pemeka Organik Menggunakan Material TiO2 dan Pewarna Dari Ekstrak Bayam - Gunawan, Bodi (UNIB Press, 2025)
Spinach leaf extract has been used as a photosensitizer in titanium dioxide (TiO₂) nanoparticles for the fabrication of dye-sensitized solar cells (DSSCs). The TiO₂ nanoparticles were synthesized via the co-precipitation method by mixing TiCl₃ with distilled water and NH₄OH. The mixture was stirred until it turned white, indicating precipitate formation. The absorbance properties of both the TiO₂ nanoparticle powder and the natural dye were analyzed using UV-Vis spectrophotometry. DSSCs were fabricated by coating TiO₂ onto indium tin oxide (ITO)-coated glass substrates using the doctor blade method, followed by immersion in the dye solution. Three DSSC devices were prepared with varying dye soaking durations: 2 hours, 4 hours, and 6 hours. The current–voltage (I–V) characteristics of each device were measured and plotted to determine their respective power conversion efficiencies. The obtained efficiencies were 0.0444% for the 2-hour soaking time, 0.0570% for 4 hours, and 0.0589% for 6 hours.